THE BEASTLEY'S MOMENT: THE METROPOLITAN POLICE OF BUENOS AIRES AND THE EXPULSION OF FOREIGNERS (1896-1904) - Albornoz, Martín; Galeano, Diego Antonio (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
The article analyzes the problem of the expulsion of foreigners suspected to be criminals or anarchists, taking as a time frame the actions of Buenos Aires police from 1896 to 1904, when Francisco Beazley was the chief of the police. Focusing on the intersection of two different historiographic traditions –one having crime and police as its object of study, and the other focused on the emergence of anarchism- research is aimed at understanding immigrant deportation mechanisms before and after the Residence Act (1902) was approved. Despite the focus is placed on measures taken by Buenos Aires police, one of the central hypothesis of this work is that understanding police action regarding immigrant expulsion requires the study of its linkages along the Atlantic coast of South America and Europe. This way, the article aims at reconstructing the map of the transnational policing, connecting Buenos Aires, Rio de Janeiro, Montevideo and Spain. With that objective, a diverse group of sources have been consulted, including consular reports, police and crime press, local newspapers and anarchists and socialist’s writings.